Fluid simulation for computer graphics - Bridson, Robert 1976- (Boca Raton, FL CRC Press, Taylor & Francis Group, 2016)
"A practical introduction, the second edition of Fluid Simulation for Computer Graphics shows you how to animate fully three-dimensional incompressible flow. It covers all the aspects of fluid simulation, from the mathematics and algorithms to implementation, while making revisions and updates to reflect changes in the field since the first edition."--Cover.
Part I. The basics. The equations of fluids -- Overview of numerical simulation -- Advection algorithms -- Level set geometry -- Making fluids incompressible -- Smoke -- Particle methods -- Part II. More types of fluids. Water -- Fire -- Viscous fluids -- Part III. More algorithms. Turbulence -- Shallow water -- Ocean modeling -- Vortex methods -- Coupling fluids and solids.
"An A K Peters Book"--Cover.
Includes bibliographical references and index.
Keywords: Computer graphics -- Mathematics; Computer animation; Three-dimensional display systems